2017
DOI: 10.1165/rcmb.2016-0259oc
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB Mediates Mesenchymal Transition, Remodeling, and Pulmonary Fibrosis in Response to Chronic Inflammation by Viral RNA Patterns

Abstract: Airway remodeling is resultant of a complex multicellular response associated with a progressive decline of pulmonary function in patients with chronic airway disease. Here, repeated infections with respiratory viruses are linked with airway remodeling through largely unknown mechanisms. Although acute activation of the Toll-like receptor (TLR) 3 pathway by extracellular polyinosinic:polycytidylic acid (poly[I:C]) induces innate signaling through the NF-κB transcription factor in normal human small airway epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(89 citation statements)
references
References 55 publications
2
87
0
Order By: Relevance
“…In contrast, intracellular viral PAMPs are detected by dsRNA helicases and kinases of the retinoic acid inducible gene -I (RIG-I)/melanoma differentiation-associated protein (MDA5) family. Upon binding their cognate PAMPs, PRR-mediated signaling produces acute oxidative injury [14], disruption of cilia function, epithelial apoptosis, disruption of epithelial barrier function [15], and activation of IIR signaling, resulting in rapid neutrophilic inflammation [16]. These pathways have been extensively reviewed [17] and modeled mathematically [18].…”
Section: The Airway Epithelial Cell As a Sensor Of Rsv Replicationmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, intracellular viral PAMPs are detected by dsRNA helicases and kinases of the retinoic acid inducible gene -I (RIG-I)/melanoma differentiation-associated protein (MDA5) family. Upon binding their cognate PAMPs, PRR-mediated signaling produces acute oxidative injury [14], disruption of cilia function, epithelial apoptosis, disruption of epithelial barrier function [15], and activation of IIR signaling, resulting in rapid neutrophilic inflammation [16]. These pathways have been extensively reviewed [17] and modeled mathematically [18].…”
Section: The Airway Epithelial Cell As a Sensor Of Rsv Replicationmentioning
confidence: 99%
“…As with the rapid activation of immediate-early IIR genes, NFκB binding recruits BRD4 to the SNAI/ZEB1/TWIST promoters and mediates ECM production and airway fibrosis [61]. Several studies have shown that small molecule BRD4 inhibitors block mesenchymal transition [16,85].…”
Section: P-tefb Plays a Role In Epithelial-mesenchymal Transition (Emt)mentioning
confidence: 99%
“…Interestingly, compared with younger mice with asthma, older mice with asthma displayed a higher expression of pSmad3 42 , an important pathway of TGF-β1-mediated fibrosis 43 , which was also strongly enhanced by poly(I:C). Chronic poly(I:C) stimulation can stimulate NF-κB expression and epithelial-mesenchymal transition, fibrosis, and airway remodeling 44 . Taken together, these findings suggest that viral exposure could amplify the age-dependent increase in OPN, which enables airway inflammation and TGF-β1mediated remodeling and contributes to presenting a more severe phenotype of asthma of LOA.…”
Section: Discussionmentioning
confidence: 99%
“…For this study, we used a fibrosis model driven by chronic TLR3 activation induced by repetitive administration of the poly(I:C) agonist, the model representative of a viral-induced fibrosis. This innate epithelial activation model has been shown to cause significant, chronic airway fibrosis and remodeling within a 30 day period 31 . Previous assessment of this model involved histology of regional areas of the lung.…”
Section: Discussionmentioning
confidence: 99%
“…A repetitive poly(I:C) challenge murine model of airway remodeling and subepithelial fibrosis served as the lung fibrosis model 31 . Animal experiments were performed according to the NIH Guide for Care and Use of Experimental Animals and approved by the University of Texas Medical Branch (UTMB) Institutional Animal Care and Use Committee (approval no.…”
Section: Methodsmentioning
confidence: 99%